Does OCI Presentation for Equity Financial Assets Matter?. Issue 4 (12th September 2022) - Zang, Zeting; Kabir, Humayun; Scott, Tom
Abstract: One significant change in International Financial Reporting Standard (IFRS) 9 Financial Instruments is how firms' equity financial assets (EFA) are presented. The default EFA presentation is at fair value through profit or loss (FVTPL); however, IFRS 9 allows irrevocable presentation of fair value through other comprehensive income (FVTOCI). Although FVTOCI is the most common presentation for EFA both before and after IFRS 9, there is a significant increase in the use of FVTPL post IFRS 9 via an improvement in disclosure clarity about presentation location. To assess the impact of EFA presentation, we recalculate profitability ratios assuming different presentation locations and find some evidence of significant differences for financial firms. We also provide descriptive evidence that EFA use and presentation behaviour vary between sectors and firm size quartiles. This study expands the literature on EFA accounting and provides a timely response to IFRS 9 post‐implementation review by shedding some light on EFA use and presentation locations under IFRS 9. Abstract : One significant change in IFRS 9 is how firms. equity financial assets (EFA) are presented. Although FVTOCI is the most common presentation location for EFA before and after IFRS 9, there is significant increase in the use of FVTPL post‐IFRS 9 and improvement in disclosure clarity about presentation location. Any impact on financial ratios is likely restricted to financial firms.